DIMENSIONAL ACCURACY OF FUSED FILAMENT FABRICATION BY CASSAVA ADHESION ON PRINTING PLATFORM - Ramli, F.R.; Nazan, M.A.; Alkahari, M.R.; Abdullah, M.A.; Sudin, M.N.; Herawan, S.G. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This paper examined the dimensional accuracy of fused filament fabrication (FFF) model when cassava based adhesive was moistened onto the printing platform. The cassava based adhesive was prepared by mixture of 0.1M of hydrochloride (HCl) , 0.1 g of cassava starch and 0.15g sodium borate and the bonding strength of 3D printing part and glass with cassava based adhesion were obtained using ASTM D2095. Test specimens model of 100×30×10mm3 with centre cavity of 24x60mm2 were fabricated by Pursa i3 machine using both ABS and PLA and varying side angles with by cassava pre-moisted on the heated printing platform. The dimensional accuracy of the warping deformations of curling, overhang, side and internal shrinkage were measured. The results show that cassava based adhesives has generally successfully reduced the curling effect for both ABS and PLA material. There was a downward trend for increasing side angles for curling, overhang and internal shrinkage but for all test specimens has lower percentage error of less than 10%. In addition. the internal shrinkage had not be affected by variation change of angles. Though the finding shows warping deformation still existed in FFF, cassava starch adhesive can be recommended as promising replacement to synthetic based adhesive.